Work! : best of office design - Schulz, Annika ([Berlin] : Braun, 2008)
The illustrated volume Work. Best of Interior Design of the new Best of series focuses on the design of modern office spaces and buildings. Starting with traditional cubicles, on to custom designed work environments, and ending in open team spaces and interaction areas, this title presents all kinds of new space concepts in the realm of work. Creativity is given no limits: An exciting interplay of color and light, strict steel-and-glass structure or the self-aware building of the natural material wood on 400 pages the reader finds 40 projects in the most contrasting styles and designs from around the world.
Includes index.
Keywords: Office decoration; Offices -- Designs and plans; Office buildings